2022
DOI: 10.3390/jcm11164770
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Nerve Changes Observed by In Vivo Confocal Microscopy in Patients Receiving Oxaliplatin for Colorectal Cancer: The COCO Study

Abstract: An objective method of early identification of people at risk of chemotherapy-induced peripheral neuropathy is needed to minimize long-term toxicity and maximize dose intensity. The aims of the study were to observe corneal nerve microstructure and corneal sensitivity changes and peripheral neuropathy in patients receiving oxaliplatin, and to determine its association with corneal parameters at different stages of treatment and assess utility as non-invasive markers to detect and monitor peripheral neuropathy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…While deep learning algorithms continue to evolve and be developed to enhance nerve segmentation and evaluation, most are limited to research settings and require further validation before implementation in clinical practice 19 , 20 . A software using a customised deep learning-based approach known as deepNerve has recently been developed and used for animal and clinical human studies 21 , 22 , demonstrating the promising potential of artificial intelligence in this area.…”
Section: Introductionmentioning
confidence: 99%
“…While deep learning algorithms continue to evolve and be developed to enhance nerve segmentation and evaluation, most are limited to research settings and require further validation before implementation in clinical practice 19 , 20 . A software using a customised deep learning-based approach known as deepNerve has recently been developed and used for animal and clinical human studies 21 , 22 , demonstrating the promising potential of artificial intelligence in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic sensitivity and several associations between the severity of intraepidermal nerve fiber loss, severity of NCS or QST abnormalities in oxaliplatin-treated patients vs. neurpathic pain were studied (8)(9)(10). Regarding CCM, different studies have shown corneal nerve microstructure and corneal sensitivity changes in patients receiving oxaliplatin (15). In addition, imaging of the corneal sub basal nerve plexus was reported as biomarker for nerve regeneration in CIPN (16).…”
Section: Introductionmentioning
confidence: 99%